1998
DOI: 10.1007/bf02385377
|View full text |Cite
|
Sign up to set email alerts
|

The limit of detection improvement in TLC determination of uranium and thorium in the presence of other metal ions

Abstract: The limit of detection (LOD) improvement in TLC determination of uranium and thorium in presence of other metal ions is presented in this paper. The mobile phase system contains iso-propyldithiophosphotic acid (i-PrDTP), as a complexing agent, in order to differentiate the studied species by modifying their retention. The paper reports the successful separation and the quantitative determination of uranium and thorium in the presence of other metal ions in the concentration range 2.5 30 p~g/p~l.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Therefore, it is necessary to develop simple methods with excellent sensitivity and specificity to detect and harvest uranyl ions. Various analytical methods have been used to detect uranyl ions, including optical spectroscopy (e.g., fluorescence spectroscopy, 11 spectrophotometry, 12 optode, 13 and Raman spectroscopy 14,15 ), mass spectrometry, 16 separation methods, 17 and electrochemical analysis. 18−20 Recently, various methods using biological molecules to detect uranyl ions have also been developed.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is necessary to develop simple methods with excellent sensitivity and specificity to detect and harvest uranyl ions. Various analytical methods have been used to detect uranyl ions, including optical spectroscopy (e.g., fluorescence spectroscopy, 11 spectrophotometry, 12 optode, 13 and Raman spectroscopy 14,15 ), mass spectrometry, 16 separation methods, 17 and electrochemical analysis. 18−20 Recently, various methods using biological molecules to detect uranyl ions have also been developed.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to develop simple methods with excellent sensitivity and specificity to detect and harvest uranyl ions. Various analytical methods have been used to detect uranyl ions, including optical spectroscopy (e.g., fluorescence spectroscopy, spectrophotometry, optode, and Raman spectroscopy , ), mass spectrometry, separation methods, and electrochemical analysis. Recently, various methods using biological molecules to detect uranyl ions have also been developed. , Zhou et al previously reported an α-helical peptide, called super uranyl binding protein or SUP, that binds UO 2 2+ with femtomolar affinity and remarkable selectivity, better than 10,000-fold affinity over other common metal ions. The X-ray structure of this peptide was determined with both UO 2 2+ absent (PDB ID: 4FZO) and bound (PDB ID: 4FZP) and revealed that the SUP conformation changes only slightly in response to UO 2 2+ -binding.…”
Section: Introductionmentioning
confidence: 99%
“…-The thin layer chromatography (Hodisan at al., 1998) is also used for the determination of uranium and thorium in presence of other metal ions using the iso-acid propyldithiophosphoric (PRDTP-i) in mobile phase as a complexing agent to differentiate between the species studied by modification of their retention time.…”
Section: Introductionmentioning
confidence: 99%
“…In view of this extraction and determination of U(VI) from surface and ground water has become a matter of great interest. 1,2 The literature citation revealed that there are various analytical techniques for the estimation of uranium which include thin layer chromatography, 3 gravimetry, 4 titrimetry, 5 fluorimetry, 6,7 potentiometry, 8 polarography, 9 X-ray fluorescence, 10 inductively coupled plasma mass spectrometry. 11 In addition, spectrophotometric methods have also been employed to determine U(VI) in presence of thorium(IV), 12 ore leachates, 13 natural waters, [14][15][16] process streams of a uranium extraction plant 17 and soil.…”
Section: Introductionmentioning
confidence: 99%